An innovative biotransformation to produce resveratrol by Bacillus safensis. Issue 27 (17th May 2019) - Hu, Xiaoyan; Liu, Yexue; Li, Dengke; Feng, Wei; Ni, Hanmeng; Cao, Shan; Lu, Fuping; Li, Yu
Abstract : The transformation ability of Bacillus safensis and the antimicrobial activity of resveratrol. Abstract : Resveratrol is considered as a potential food supplement, cosmetic ingredient and nutraceutical. In this study, resveratrol was produced by biotransformation successfully. In detail, a β-glucosidase producing strain was isolated and identified as Bacillus safensis, and it could convert polydatin to resveratrol efficiently and rapidly. Further research showed that the conversion rate to resveratrol reached 93.1% in 8 h at 37 °C. The production of resveratrol was confirmed by HPLC, LC-MS and 1 H-NMR to identify its structure and it was verified to possess antibacterial properties especially against Escherchia coli. To illustrate the resveratrol transformation mechanism, several glucosidases from B. safensis CGMCC 13129 were expressed and analyzed. The results showed that BGL4 and BGL5 had higher transformation activity compared with other tested glucosidases. This research provides a novel approach to produce resveratrol, and would promote the application of resveratrol in health-promoting pharmaceutical and food products.